Zonal text processing. - Yatsko, Viatcheslav (Digital Scholarship in the Humanities, 2016)
The article describes methodology of zonal text processing based on interpretation of Bradford's law in terms of geometric progression. The methodology involves dividing the text into three zones (J, J, J) and finding their composition. To verify the value of Bradford multiplier two methods that evaluate distribution of stop words across the three zones are used. The concept of zonal-correlational processing that implies contrastive analysis of J zones of two or more texts for the purpose of authorship attribution and classification is formulated and tested. To address the problem of difference in text sizes the concept of logarithmic equalizing is proposed.